An Expanded Analysis of Pharmacogenetics Determinants of Efavirenz Response that Includes 3′-UTR Single Nucleotide Polymorphisms among Black South African HIV/AIDS Patients - Swart, Marelize; Evans, Jonathan; Skelton, Michelle; Castel, Sandra; Wiesner, Lubbe; Smith, Peter J.; Dandara, Collet (Frontiers in Genetics, 2016)
Introduction: Efavirenz (EFV) is a non-nucleoside reverse transcriptase inhibitor prescribed as part of first-line highly active antiretroviral therapy in South Africa. Despite administration of fixed doses of EFV, inter-individual variability in EFV plasma concentrations has been reported. Poor treatment outcomes such as the development of adverse drug reactions or treatment failure have been linked to EFV concentrations outside the therapeutic range (1 - 4 µg/mL). The drug metabolising enzyme (DME), CYP2B6, is primarily responsible for EFV metabolism with minor contributions by CYP2A6, CYP3A4, CYP3A5, UGT2B7 and CYP1A2. Genes coding for DMEs have been shown to be regulated by microRNAs through targeting the 3'-untranslated region. Genetic variation in the 3'-UTR, in addition to genetic variation in the coding regions, could potentially be used to explain a larger proportion of the inter-individual variability observed in drug response. Methods: SNPs in CYP1A2, CYP2B6, UGT2B7 and NR1I2 (PXR) were selected for genotyping among 222 Bantu-speaking South African HIV-infected patients receiving EFV-containing HAART. This study is a continuation of earlier pharmacogenetics studies emphasizing specifically the role of genetic variation in the 3'-UTR of genes which products are either pharmacokinetic or pharmacodynamic targets of EFV. Results: In addition to CYP2B6 c.516G>T and c.983T>C SNPs, the CYP2B6 c.1355A>G SNP was identified as pharmacogenetics determinant of EFV concentration among CYP2B6 intermediate and extensive metabolisers (carriers of either c.516G/G+c.983T/T or c.516G/G+c.983T/C or c.516G/T+c.983T/T genotypes). NR1I2 c.522C>T and NR1I3 c.239-1089T>C SNPs were predictors of EFV concentration among CYP2B6 poor metabolisers (carriers of either c.516T/T or c.983C/C or both c.516G/T and c.983T/C genotypes). Conclusion: Genotyping results provide support for comprehensive studies of genetic variation in the 3'-UTR of genes coding for DMEs and their inclusion in predictive pharmacogenomics models to get a clearer picture on correlates of drug response.